Prenatal Diagnosis of Aorto-Left Ventricular Tunnel With Dysplastic Bicuspid Aortic Valve: From Fetal Cardiac Failure to Favorable Outcome - Ba Luu Truong; Ba Luu Truong; Anne Moreau De Bellaing; Anne Moreau De Bellaing; Emmanuelle Vialle; Ayman Haydar; Pascal Vouhe; Pascal Vouhe; Pierre Simon Jouk; Gerard Blaysat (Frontiers Media S.A., 2020)
Aorto-left ventricular tunnel (ALVT) is a rare congenital heart defect. Surgery has to be performed early to avoid life-threatening complications. Prenatal diagnosis of this defect is challenging. We report a case of ALVT diagnosed in a fetus showing premature severe cardiac failure at 24 GA. The new born was operated at day 3 of life with good results. Two years later, he is still doing well recovering a complete normal cardiac function. ALVT should be suggested in front of any fetal cardiac failure. Thanks to early diagnosis, prompt neonatal management can be organized and allows positive outcome.